OC-018 Gastrin Increases Mir-222 Expression In Gastric Epithelial Cells in Vitro And Hypergastrinaemic Ins-gas Mice In Vivo. (9th June 2014) - Lloyd, K; O'Hara, A; Varro, A; Pritchard, DM
Abstract : Introduction: Gastric adenocarcinoma occurs in some patients who are infected with Helicobacter pylori . Gastrin is a cofactor in gastric carcinogenesis and elevated serum concentrations are found in the preneoplastic condition atrophic gastritis. MicroRNAs (miRNAs) are small non-coding RNAs that post transcriptionally regulate numerous mRNAs and play critical roles in cell physiology. Previous studies have suggested that H.pylori infection dysregulates miRNAs to control gastric inflammation, cell cycle progression, apoptosis and cell survival. We hypothesised that gastrin would also induce alterations in gastric miRNAs and that these may influence cancer development. Methods: Human gastric adenocarcinoma cells that have been stably transfected with the human CCK2 receptor (AGSGR ) were treated with 0.1–100 nM gastrin for 2–48 h. Small RNAs were isolated and reverse transcribed using the Qiagen miScript PCR system kit. miRNA expression profiling was determined by qPCR using miScript PCR arrays (in triplicate) and further validated using miRNA primer assays (in quadruplicate). Cycle passing threshold (Ct) was normalised to RNU62 expression and miRNA relative expression calculated using ΔΔCT method. miR-222 levels were measured in gastric mucosal scrapings from 10 week old male and female (n = 3 per group) wild-type FVB/N mice and transgenic hypergastrinaemic INS-GAS mice on the same genetic background. Comparisons were made using unpaired t-tests with Bonferroni correction, P < 0.05 was considered significant. Results: miR-376c and miR-222 were significantly overexpressed in gastrin treated AGSGR cells, by 5.2-fold [p < 0.01] and 2.3-fold [p < 0.0001] respectively. However only the increase in miR-222 expression was confirmed using qPCR. Maximal increased expression of miR-222 (9-fold [p < 0.01]) was seen after 10 nM G17 treatment for 24 h in serum free media. Increased miR-222 expression was completely reversed by pre-treatment with the CCK-2 receptor antagonist YM022 (100 nM). miR-222 expression was also significantly increased in 10 week old female and male INS-GAS mice, compared with FVB/N mice (by 5.3-fold and 2.3-fold respectively). Conclusion: Gastrin induces gastric miRNA alterations, specifically miR-222 overexpression, both in vitro and in vivo . This was fully reversed by pre-treatment with YM022 in vitro . Since miR-222 overexpression has previously been linked to decreased expression of tumour suppressor proteins such as p27 Kip1 and increased oncogenesis, these data support the hypothesis that elevated gastrin may induce pathological changes via disruption of miRNA (particularly miR-222) expression. Further studies are needed to determine the mechanisms by which gastrin-induced miR-222 overexpression affects gastric pathology. Disclosure of Interest: K. Lloyd Grant/research support from: Trio Medicines Ltd, A. O'Hara: None Declared, A. Varro Grant/research support from: Trio Medicines Ltd, D. Pritchard Grant/research support from: Trio Medicines Ltd.